Pattern of Antibiotic Use in the Perinatal Period in a Public University Hospital in Romania - Viviana Hodoșan; Cristian Marius Daina; Dana Carmen Zaha; Petru Cotrău; Adriana Vladu; Carmen Pantiș; Florica Ramona Dorobanțu; Marcel Negrău; Adriana Maghiar; Lucia Georgeta Daina (Medicina, 2022)
Background and Objectives: Antibiotics are the most frequently prescribed drugs in hospitals and their prescription is increased during pregnancy and labor. There are limited data about this issue, and the safe use of antibiotics in pregnancy and antibiotic resistance remains a concern. The aim of the study is to evaluate the use of antibiotics among pregnant women attending hospital for five years. Materials and Methods: Antibiotic consumption and treatment information of patients were retrospectively collected from a hospital software program and expressed as defined daily dose (DDD) according to the World Health Organization (WHO) methodology for inpatients between 2017 and 2021. We evaluated antibiotic prescription by name, classes, and Food and Drug Administration (FDA) categories. Results: Antibiotic consumption shows a decreasing trend between 2017 and 2019, but an increasing one between 2020 and 2021. Ceftriaxone was the most prescribed antibiotic in each year, followed by cefixime, amoxicillin, metronidazole, cefuroxime, ampicillin, and ciprofloxacin. We noticed that first- and fourth-generation cephalosporins were not prescribed to these patients. A very small percentage of women in this study received antibiotics such as aminoglycosides; fluoroquinolones were generally contraindicated in the perinatal period. A large percentage of prescriptions were antibiotics classified as category B by the FDA. The most common infections that occurred in the perinatal period were those of the kidney and urinary tract in a higher number than in other studies. Conclusions: Our study shows that many classes of antibiotics used in perinatal women belong to category B antibiotics, the most prescribed being cephalosporins. Because of insufficient safety evidence and the potential for teratogenic effects on the fetus, restricted use among the category C and D antibiotic classes was seen and anticipated. Improving maternal health requires the involvement of healthcare experts in risk assessment and evaluation of existing data for appropriate antibiotic selection, dose, duration of medication, and monitoring.